What if it is not just an additional income? Poverty risks of non-standard employment histories in Germany - Fridolin Wolf (International Journal of Social Welfare, 2024)
Abstract While the poverty risks associated with transitions to and from different forms of non-standard employment (NSE) have been studied extensively, poverty research on NSE histories remains fuzzy. Therefore, this study focuses on persons with NSE histories whose earnings contribute significantly to the household income, asking to what extent they are exposed to income poverty risks during their main career phase and examining the role of employment, family and sociodemographic characteristics. Employment histories were observed over 100.167emyears using German Socio-Economic Panel data from 2001 to 2020. A sequence cluster analysis identified four NSE clusters with increased poverty risks, namely, those with increasing and permanent low-part-time work, those who were mainly temporary agency-employed or had long episodes of fixed-term employment. Multivariate regressions considering employment-specific, care-related and sociodemographic characteristics revealed a network of cumulative disadvantages related to gender, occupational position, care obligations and structural disadvantages for those clusters.
Keywords: 330; atypical employment; employment history; in-work poverty; labour market deregulation; non-standard employment; part-time employment; temporary employment